Determinants of the buying interest of trendy Indonesian iced tea drinks in Medan city - Hajari, Vani; Ramadhani, Sri; Ikhsan Harahap, Muhammad (Universitas Pamulang, 2025)
The trend of trendy drinks in Indonesia is experiencing rapid growth. The Es Teh Indonesia brand has gone viral and reached various cities, including Medan. This study aims to analyze the influence of price, promotion, product innovation, and social media on purchasing interest in the trendy drink Es Teh Indonesia brand in Medan City. This study uses a quantitative approach with a survey method through a questionnaire to 100 respondents aged 17-30 years and above who are consumers of Es Teh Indonesia. This study analyzed the data using the linear regression method with the ordinary least squares estimator. The results of this study indicate that social media and product innovation are the most dominant variables influencing purchasing interest. This study helps understand the younger generation's choice of trendy drinks, so that marketing strategies can be created that align with current trends and the use of digital media. Abstrak Trend minuman kekinian di Indonesia mengalami pertumbuhan pesat, salah satunya ditandai oleh merek Es Teh Indonesia yang menjadi viral dan menjangkau berbagai kota, termasuk Medan. Penelitian ini bertujuan untuk menganalisis pengaruh harga, promosi, inovasi produk, dan media sosial terhadap minat beli minuman kekinian merek Es Teh Indonesia di Kota Medan. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei melalui kuesioner kepada 100 responden berusia 17-30 tahun keatas yang merupakan konsumen Es Teh Indonesia. Penelitian ini menganalisis data dengan metode regresi linear dengan estimator ordinary least square. Hasil penelitian ini menunjukkan bahwa media sosial dan inovasi produk menjadi variabel paling dominan mempengaruhi minat beli. Penelitian ini membantu memahami generasi muda memilih minuman kekinian, sehingga bisa membuat strategi pemasaran yang sesuai dengan perkembangan trend zaman sekarang dan pemanfaatan media digital.